In the background of the Radical Enlightenment: Publishers - Translators - Librarians - Journalists (1770-1820). - Mulsow, Martin (Libertinage et Philosophie à l'Époque Classique (XVIe-XVIIIe Siècle), 2026)
This article focuses on the little-known figures of the Age of Radical Enlightenment in Germany between 1770 and 1820, notably publishers, translators, librarians, and journalists who supported the clandestine dissemination of deist or atheist ideas. It highlights figures such as Franz Heinrich Bispink, a former monk turned publisher and librarian; Christian Ludwig Paalzow, translator and compiler of radically antireligious texts; as well as Julius Friedrich Knüppeln, journalist and writer engaged in underground political literature. These actors, often socially and economically precarious, played a central role in the circulation of radical ideas by circumventing censorship and creating support networks. The study emphasizes that the material and social infrastructure of this radical thought operated according to its own logic, where collaboration and the reappropriation of texts were essential in the struggle against religious and political orthodoxy.